OPTIMALISASI MINAT MENABUNG NASABAH PADA TABUNGAN BAROKAH DI PT. BPRS BHAKTI SUMEKAR CABANG PAMEKASAN - Mujibno Mujibno; Ryan Aidil Hakim; Abdul Wahid; Amiruddin Amiruddin (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
This study aims to determine the optimization of customer interest in barokah savings at PT. BPRS Bhakti Sumekar. Barokah savings are savings or customer funds deposits in the form of rupiah savings with a wadhi'ah yadh dhamanah contract, namely as a pure deposit that will help manage your funds to be more blessed. This study uses descriptive qualitative methods with data collection techniques through interviews, the results of observations with case study designs from interviews with related and responsible parties that optimizing customer interest in barokah savings at BPRS Bhakti Sumekar Pamekasan Branch are quite good, where from From year to year, the number of customers has increased, with the assistance of the marketing department and very good socialization and door-to-door marketing strategies, so that they are helped and influential. The optimization has also been carried out carefully with caution both in terms of service, especially in friendliness in communicating with customers and always competent and consistent in determining the schedule that has been determined between the customer and the marketing party.